Different gamma delta T-cell receptors are expressed on thymocytes at different stages of development. - Ito, K (1989)
We have analyzed the structural diversity of the murine gamma delta T-cell receptor (TCR) heterodimer expressed on CD4- CD8- thymocyte populations and on TCR gamma delta-expressing hybridomas derived from thymocytes of fetal, newborn, and adult mice. We found that CD4- CD8- thymocytes derived from mice of different pre- and postnatal age preferentially express a gamma delta TCR encoded by different subsets of gamma and delta gene segments. This age-dependent differential expression of gamma delta TCR on thymocytes seems to be accomplished in part by a specific control of rearranged gamma genes operating at the level of transcription and/or RNA stability. We discuss the implications of these findings with respect to the recognition roles of the gamma delta TCR.